Flexible lateral-bridged ZnO nanowire UV sensor for focal-plane image sensor application. (23rd October 2018) - Zhao, Lihuan; Gao, Zhiyuan; Zhang, Jie; Lu, Liwei; Zou, Deshu
Abstract: We report a large-format flexible UV image-sensing array consisting of 32 × 32 sensors based on lateral-bridged ZnO nanowires (NWs). Systematic investigations for the array have shown that 100% of the sensors showed a response with high uniformity (the nonuniformity of photocurrent was 44%) and high average light–dark current ratio (∼1.1 × 10 5 ), average responsivity (∼923 A/W), and average detectivity (∼2.5 × 10 14 Jones). The pixel size is 60 × 125 µm 2 and pixel pitch is 150 µm. The array also exhibited excellent flexibility and electrical stability under the bending state. The results indicate that the sensor array offers exacting possibilities for fabricating flexible UV focal-plane image sensors.